Advancing the physical chemical understanding of coffee foam - Papageorgiou, Christos (2024)
Coffee foam is one of the important sensory characteristics of brewed coffee and defines the quality of a cup of coffee. However, there are no published mechanisms that describe the stability of the coffee foam system. The present PhD thesis aimed to advance the physical-chemical understanding of coffee foams in the pursuit of manufacturing high quality coffee beverages.